Can Asia Overcome the IMF Stigma? - Ito, Takatoshi (American Economic Review, 2012)
Asian countries still have the IMF stigma, which originates from the experiences of the Asian crisis of 1997-98. The feeling of being unfairly treated grew even stronger afterward. The Asian countries built large foreign reserves, carried out structural reforms, and became even stronger than pre- crisis period. Asians are confident in not repeating the same mistake of falling into a crisis with too much external borrowing. Whether IMF can entice Asia to new precautionary liquidities facilities remains uncertain. Asia may choose either to focus on completing a regional safety net or to engage in IMF, demanding for a greater voice and votes.